Comportamento suicida : um olhar sobre os casos notificados e os cuidados ofertados de 2018 a 2022 no município de Vila Velha (ES) - Roffes, Amanda Andreatta (2024)
Suicidal behavior, considered a global public health problem since the 20th century, is understood as a multifactorial and multidetermined phenomenon, which goes through varied trajectories and affects all genders, age groups and ethnicities. This study aimed to comprehend the cases of suicidal behavior and the care offered to different age groups in a municipality in Grande Vitória (ES), from 2018 to 2022. To accomplish this, we aimed to characterize the cases of people who attempted and died by suicide registered by the municipality, to compare the cases of people who attempted and died by suicide between the years of 2018 and 2022, and to understand the history of health, illness and care recorded for people with suicidal behavior treated by mental health services. A qualitative and quantitative study was conducted based on an analysis of the databases from the self-inflicted violence notification forms and Death Certificates (DC) made available by the Epidemiological Monitoring Service and the medical records selected by the municipality's mental health services. The quantitative data from the forms and DCs were analyzed using SPSS software and the qualitative data from the medical records were analyzed using thematic content analysis. The results showed that the prevalence of self-inflicted injuries was female, aged between 10 and 19, brown, and caused by poisoning/intoxication. The Hospital Infantil e Maternidade Azir Bernardino Alves (HIMABA) was the main notifier, and referral to the Health Network was the most common. In terms of mortality, there was a prevalence of males, aged between 30 and 59, who had committed hanging. When comparing the years of the study, there was an increase in notifications of self harm and stability in the number of deaths. In the analysis of the medical records, it was found that cases with a satisfactory outcome had greater adherence to collective proposals and, in contrast, cases with an unsatisfactory outcome had a prevalence of individualized monitoring. 8 This research, by offering an overview of suicidal behavior in Vila Velha, allows the Public Power to adopt strategic measures for care, especially because it has highlighted the prevalence of suicidal behavior in younger age groups than in the national scenario, because of the knowledge of gaps identified in notifications and because it provides an overview of the care offered, highlighting obstacles and potentialities